Impaired orexin receptor expression in the Kölliker–Fuse nucleus in sudden infant death syndrome: possible involvement of this nucleus in arousal pathophysiology. (2nd August 2016) - Lavezzi, Anna Maria; Ferrero, Stefano; Roncati, Luca; Matturri, Luigi; Pusiol, Teresa
Abstract : Objectives: As well known, the sudden infant death syndrome (SIDS) is characterized by the sudden death of a seemingly healthy infant during sleep, frequently resulted from a deficit in arousal phase. Awakening from sleep requires a fully developed and functioning neuronal respiratory network to modulate the ventilation as needed. The pontine Kölliker–Fuse nucleus (KFN) plays a pivotal role in breathing control, thanks to its interconnections with the widespread serotonin and noradrenaline neurons in the brainstem. Numerous studies to date have focused on the implication of orexin, a neuropeptide synthesized by neurons of the lateral hypothalamus, with major projections to the brainstem raphé nuclei and locus coeruleus, in arousal, a neurobiological process closely linked to breathing modifications. The aim of our research has been to demonstrate that also the KFN is a fundamental component of the orexin system, actively involved in arousal. Methods: We have evaluated the expression and distribution of the orexin receptors (orexin-1 and orexin-2 receptors) particularly in the rostral pons, where the KFN is located, of 25 SIDS cases and 18 controls. Results: An intense orexin-1 innervation around the KF neurons has been detected in almost all the controls and only in 20% of SIDS cases. Discussion: On the basis of these results, we believe that: (1) the KFN plays a leading role not only in providing a regular breathing rhythm but also in the coordination of the sleep-to-wake transition; (2) a defective orexin expression in the KFN could prevent arousal, thus assuming a crucial importance in causing SIDS.